SLOW STROKE BACK MASSAGE UPAYA MENGURANGI NYERI LUKA JAHITAN PERINEUM PADA IBU POSTPARTUM HARI KEDUA - Anisa Sevi Oktaviani; Misrina Retnowati; Ernawati (Jurnal Bina Cipta Husada, 2023)
One of the pain rates in postpartum mothers is caused by perienal wound pain. Perineal lesions occur in almost all vaginal deliveries, whether they are intentional injuries with an episiotomy or rupture resulting from childbirth. Slow Stroke Back Massage (SSBM) effectively reduces pain by stimulating the body to release endorphin compounds that can eliminate pain naturally so that you feel more comfortable. The purpose of this study is to determine the effect of slow stroke back massage as an effort to reduce perineal suture wound pain in postpartum mothers on the second day. The research method uses Quasi Experimental with Pre And Post Test Without Control design. The samples in this study were all mothers who experienced perineal rupture in postpartum mothers on the second day who became patients for postpartum maternal care at the AmbeR Mom and Baby Care clinic totaling 33 postpartum mothers. Data analysis using Wilcoxon test. The results showed a significant reduction in pain from respondents. Conclusion there is an effect of slow stroke back massage as an effort to reduce perineal suture wound pain in postpartum mothers on the second day. Keywords: perineal pain, slow stroke back massage, postpartum